Case Report: A novel ELMOD3-ALK and EML4-ALK double-fusion responses to neoadjuvant alectinib in a lung adenocarcinoma patient - Huang, Kaili; Li, Wen; Xue, Yinyin; Peng, Lei; Wu, Qiang; Zhou, Qinghua (Frontiers in Pharmacology, 2025)
BackgroundAnaplastic lymphoma kinase (ALK) rearrangements account for approximately 3%–5% of non-small cell lung cancer (NSCLC), and the echinoderm microtubule-associated protein-like 4 gene (EML4) and ALK fusion (EML4-ALK) is the most common ALK rearrangement in NSCLC patients. However, double-ALK fusion is extremely rare in clinical practice. Herein, we first report a lung adenocarcinoma patient with the coexistence of a novel subfamily 3 of ELMOD (ELMOD3)-ALK, EML4-ALK double fusion that is sensitive to alectinib target therapy.Materials and methodsHematoxylin–eosin (H&E) staining, immunohistochemistry (IHC), and next-generation sequencing (NGS) were performed on biopsy samples.ResultsThe IHC analysis confirmed positive expression of ALK protein. NGS revealed a novel ELMOD3-ALK and EML4-ALK double fusion. The patient was sensitive to alectinib as neoadjuvant therapy and achieved a major pathological response (MPR), which was confirmed by the postoperative pathology diagnosis. To date, the patients’ disease-free survival (DFS) has exceeded 4 years without any significant symptoms of toxicity.ConclusionThis is the first report of one lung adenocarcinoma patient with a novel ELMOD3-ALK, EML4-ALK double-ALK fusion. This double-ALK fusion variant is sensitive to alectinib, suggesting patients with an ELMOD3-ALK, EML4-ALK double-ALK fusion could achieve clinical survival benefit from alectinib.